New versatile synthesis for low dimension superparamagnetic YBa2Cu3O7−x nanoparticles. Issue 12 (15th August 2017) - Nasui, M.; Mos, R.B.; Gabor, M.S.; Petrisor, T.; Tomolea, A.; Ware, E.; Goga, F.; Mesaros, A.; Ciontea, L.
Abstract: This paper describes the synthesis and characterization of YBa2 Cu3 O7−x (YBCO) nanoparticles obtained through an environmentally friendly chemistry approach. Y-, Cu- acetates and Ba trifluoroacetate were used for the synthesis of the precursor gel. Moreover, sucrose and pectin reagents were added as chelating agents inducing the formation of small size oxide nanoparticles. The thermal decomposition process of the precursor powder was investigated by thermal analysis correlated with mass spectrometry. The chemical nature, structure and morphology of the particles were investigated by X-Ray diffraction (XRD), Transmission Electron Microscopy (TEM) and Fourier Transform Infrared Spectroscopy. According to XRD analysis the nanoparticles have an orthorhombic structure and the average diameter between 18–30 nm, additionally confirmed by TEM measurements. The superparamagnetic behavior at room temperature of the YBCO nanoparticles has been clearly evidenced by magnetization measurements. Furthermore, the effect of the annealing atmosphere on the magnetic properties has been studied.